Implementasi Pendekatan Saintifik Dalam Pembelajaran PAI: Strategi Guru Berbasis Problem-Based Learning - Munada, Inayatul Umah; Fitri Hilmiyati; Siti Ngaisah; Wasehudin; Rifyal Ahmad Lughowi (Mu'allim, 2025)
The scientific approach in Islamic Religious Education aims to increase students' understanding through critical and creative thinking processes. Strategies that can be used by students include Problem-Based Learning (PBL), which focuses on students as the center of learning. This research aims to 1) analyze teacher strategies in optimizing PBL in PAI learning in Class XI of SMAN 1 Petir and 2) analyze the challenges faced in implementing PBL in PAI Learning in Class The research method used is a qualitative method, the data collection technique is through observation, interviews with PAI teacher informants/respondents at SMAN 1 Petir and documentation. The results of this research are 1) The teacher's strategy for optimizing PBL in PAI learning at SMAN 1 Petir is by guiding students through each stage of PBL, providing clear instructions at each stage and integrating technology into learning, such as the use of digital media; videos, powerpoints and the internet to explore teaching materials to make them broader and more varied so as to increase the effectiveness of the learning process and increase student activity in each learning process. 2) The challenges that occur in implementing PBL are the lack of student participation, especially in group discussions and time management during the learning process, because PBL learning has many learning stages so it requires quite a long time